Reason to believe: religiosity, resilience, and self-efficacy among Malaysian Indian adolescent - Ganaprakasam, C.; Selvaraja, T.; Michael, J.; Nithlavarnan, A. (My University, 2020)
The emerging incidence of mental health-related illness such as depression, suicide, and deliberate self-harm has elevated gradually among Malaysian Indian adolescents. This disorder constitutes a significant health risk which leads to further exploration of protective factors. Thus, the purpose of this study is to investigate the relationship between religiosity, resilience, and self-efficacy among Malaysian Indian adolescents. Therefore, a sample of 86 respondents (40 males, 46 females) has been selected by a purposive sampling method to complete the questionnaire. This study utilized, Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ), Brief resilience Scale (BRS), and Self-efficacy for Self-regulated Learning Scale to obtain data and has analyzed using the correlation method. The finding of this study revealed a significant positive relationship between religiosity, resilience, and self-efficacy among Malaysian Indian adolescents. The result showed that religion is an essential phenomenon in adolescents' lives. A few limitations and recommendations for the future study included at the end of this paper.
Keywords: Religion; Resilience; Self-Efficacy; Malaysian Indian adolescents